The expanded roles of quantity surveyor in assessing the usage of big data - Azman, Nur Athirah (2023)
Big data is the process of gathering large amounts of data and analyzing it thoroughly to generate significant findings. By extracting the vast amount of data acquired, a few possibilities in the form of valuable insights may be produced. Despite this, full research focusing on the potential application of big data, particularly in the construction sector, has not been done. Therefore, the expanded roles of Quantity Surveyors in assessing the usage of big data have become increasingly significant in the field of construction and project management. The research aim to establish the big data roles in the Quantity Surveyor profession. This study also focused on identifying the roles of big data in Quantity Surveying field, determine the challenges faced by QS in exposing of big data and suggest QS preparations to adopt and operate the big data technology. A quantitative approach is used in this research and the data collected by using questionnaires survey to Quantity Surveyors consultant in Selangor, which allowed for comprehensive data collection.